A Review of Sensory Feedback in Upper-Limb Prostheses From the Perspective of Human Motor Control - Sensinger, Jonathon W.; Dosen, Strahinja (Frontiers in Neuroscience, 2020)
This manuscript reviews historical and recent studies that focus on supplementary sensory feedback for use in upper limb prostheses. It shows that the inability of many studies to speak to the issue of meaningful performance improvements in real-life scenarios is caused by the complexity of the interactions of supplementary sensory feedback with other types of feedback along with other portions of the motor control process. To do this, it frames the question of supplementary feedback from the perspective of computational motor control, providing a brief review of the main advances in that field over the last twenty years. It then separates the studies on the closed-loop prosthesis control into distinct categories, which are defined by relating the impact of feedback to the relevant components of the motor control framework, and reviews the work that has been done over the last 50+ years in each of those categories. It ends with a discussion of the studies, along with suggestions for experimental construction and connections with other areas of research, such as machine learning.